Single Agent And Synergistic Activity Of Latex C-Serum With Led Red Light In Cancer Cell Lines - Yang, Kok Lee (2021)
Hevea brasiliensis rubber latex dialysed C-serum supernatant (DCS) sub-fraction has been reported to possess potential anti-proliferation activities against specific human breast (MDA-MB-231) and liver (HepG2) cancer cell lines through autoschizis cell death pathway. Further investigations on DCS treatment (concentrations ranged between 0 to 100 μg/mL) on anti-proliferative effect in this study have shown that IC50 of DCS was at 8.81 μg/mL and 22.12 μg/mL for DBTRG (human brain glioblastoma) and MKN74 (human gastric tubular adenocarcinoma), respectively. Although DCS showed specificity in cancer cell lines based on cell viability assays, its genotoxicity effects are important in view of its employment in human subjects if it would be developed into an anti-cancer drug.